Back contact modification of the optoelectronic device with transition metal dichalcogenide VSe2 film drives solar cell efficiency - Yu Zeng; Zhan Shen; Xu Wu; Dong-Xiao Wang; Ye-Liang Wang; Ya-Li Sun; Li Wu; Yi Zhang (Journal of Materiomics, 2021)
VSe2 is with high electrical conductivity and high work function, thus it is beneficial for the carrier transport in the optoelectronic devices. However, the performance and mechanism of its effect on the photoelectronic devices conversion efficiency is still beyond understood. In this work, we fabricate VSe2 film between back contact and absorber layer Cu2ZnSn(S,Se)4 (CZTSSe) film. We demonstrate that the VSe2 film in back contact region increases solar cell efficiency by 39%. Besides improving the carrier transport in the back contact region, the increasing can also be attributed to the reduction of the decomposition reaction of CZTSSe during the nucleation of CZTSSe as VSe2 fabricated between back contact and absorber layer. The present work not only provides an effective method to improve the performance of the optoelectronic device, but also shows an attractive application of metallic TMDs in optoelectronic device and solar cell energy generation.